Pengaruh Ekspektasi Akademik, Umpan Balik Konstruktif, dan Panduan Pembelajaran Terstruktur terhadap Kemampuan Numerasi ditinjau dari Data ANBK 2023 - Misba, Muhammad Faathir Husain; Nurfadilla, Nurfadilla (Al Asma: Journal of Islamic Education, 2025)
Numeracy is a crucial competence that remains a challenge at the primary education level in Indonesia. National and international assessments revealed that many students struggle to understand and apply mathematical concepts in real-life contexts. This study aimed to analyze the influence of students' perceptions of teachers' roles on their numeracy skills, focusing on three aspects: academic expectations, constructive feedback, and structured instructional guidance. A quantitative approach was used with multiple linear regression analysis, utilizing secondary data from the 2023 National Computer-Based Assessment (ANBK), involving a sample of 164,260 elementary and Islamic elementary school students from various regions in Indonesia. The findings showed that all three variables significantly influenced students’ numeracy skills, with an R² value of 0.105. Among the predictors, structured instructional guidance had the greatest contribution to numeracy scores, followed by constructive feedback and academic expectations. These results indicate that structure, clarity, and support provided by teachers play a vital role in improving students’ numerical literacy. The study concluded that strengthening teachers’ capacity to deliver systematic guidance, communicate high expectations, and provide constructive feedback is essential to sustainably enhance primary students’ numeracy competence.